FUNCTIONAL BEAM RESEARCH METHODS IN THE DIAGNOSIS OF ABNORMAL MOBILITY OF KIDNEY - A. G. Tonyan; A. S. Tatevosyan; A. A. Khalapyan; V. L. Medvedev; A. V. Pomortsev (Исследования и практика в медицине)
Abstract:Introduction. Abnormal mobility of kidney - a combination nephroptosis with abnormal rotation in one or more static state. The main beam is at present diagnostic methods. Only ultrasound has the functionality, the ability to use polypositional.The purpose of the study. Development of functional radiological methods of diagnosis of pathological mobility of the kidney and its complications.Research methods. The methods of determining the angle of rotation according to the kidney excretory urography performed in wedge and orthostasis, ultrasound sonography, Doppler, dynamic indirect kidney scan and computed tomography. Statistical processing of the data using the package STATISTICA 6.0 software licensing and computer programs, correlation analysis, frequency and multiple correspondence analysis.The main results. To determine the location of each case properly distributed in accordance with the classification matrices further method was used polypositional ultrasound, which allowed to determine the position of the patient, which revealed significant correlated with the RMS, hemoand urodynamic changes. Application rentgenradiological diagnostic methods in the corresponding position of the fixed kidney complications pathological mobility.The main conclusions. The combination of ultrasonic, radiographic, radioisotope diagnostic PMK and its complications allows us to supplement the information content of these studies and to expand the diagnostic value of each of them. An integrated approach to the implementation of diagnostic tests will improve the efficiency of the treatment of complications PMK, reduce material costs, which in turn will improve the quality of treatment of patients with this pathology.